(untitled) (Al-Academy, 2023)
The issue of communication and communication is receiving increasing attention in both contemporary studies and educational literature, and these studies emphasize the importance of studying communication within the classroom, which inevitably applies to the importance of relationships and tensions in the field of teaching art in particular because it is an emotional field that provides an opportunity for communication competencies and skills to be prominent and take Its wide scope, both among the students themselves and between teachers and students. The means of communication are the vessel in which the cultural relations and the commonalities between people revolve. The process of building relationships between students depends in many aspects on what they possess of these competencies and on the mechanisms of their work in the educational environment. In this research, the researchers deal with communication, and then it is a communication process between students, which must be fragmented and highlighted in a way that allows it to be employed as an educational stimulus that contributes to achieving the greatest amount of the process of acquiring educational and technical experiences inside and outside the classroom, and in a way that contributes to the achievement of educational goals. To the fullest.Studying the topic of research on studying the topic of study in exchange for research in the theoretical study is very beautiful in return for obtaining an opportunity in exchange for an opportunity to study in art education lessons, and horseback riding. Direct and descriptive about it.